Teaching Learning Process Of English At SMP N 2 Gatak :A Micro Ethnography - Yulia, Fajar (2012)
this research aimed at describing the teaching learning process of English at second year at SMP N 2 Gatak. It is conducted to describe the objective learning, the type of syllabus, the material, the methods of teaching, the strengths and weaknesses of teaching learning process. In this research the data are derived from event, information and document. There are three method of collecting data, the data namely: interview, observation, and document. The data achieved from information related to the teaching learning proc ess of English at SMPN 2 Gatak , the teacher's attitude and interview. The writer takes the teacher who teaches the second year at SMP N 2 Gatak as subject of the research. The writer uses descriptive qualitative especially ethnography in analyzing the data . The result of this study are as follows: 1) The learning objective of teaching English is to develop communicative competence in four skills languages namely reading, writing, listening and writing , 2) The teacher used thematic syllabus, 3) The material, the teacher taken from textbooks LKS "Media Pintar" published by Percada , 4) The teacher used eclectic methods, the combined three methods, namely Grammar Translation Method (GTM), Total Physical Response (TPR) and Cooperative Learning , 5) The evaluation system, the teacher used two techniques. F irstly, the teacher taken from daily test and task. Secondly, the teacher taken from m mid test and final test, 6) The strengths in teaching English are the objective of learning, material, method, media, teacher role and students role and t he weaknesses found is the exercise is not various. In addition the teacher used indonesi more often than English.